Three New Species of Ferns (Pteridophyta) from Mesoamerica - Rojas Alvarado, Alexander (2017)
In this research three new species of ferns of the Polypodiales Order are described: Ctenitis leonii A. Rojas, Elaphoglossum karinae A. Rojas and Pecluma celaquensis A. Rojas. Ctenitis leonii is characterized by its apical stipe scales marginally erose to ciliate, blade surfaces with two types of hairs present in both surfaces, ones 0.7 - 1.5 mm long and not glandular, the others 0.3 - 0.5 mm long and glandular and indusia are absent. Elaphoglossum karinae differs from Elaphoglossum dissitifrons Mickel by shorter rhizome, longer and relatively narrower rhizome scales, they lanceolate to linear-lanceolate and blackish costal scales. Pecluma celaquensis is similar to Polypodium martensii Mett., but differs by its thinner rhizome, smaller rhizome scales and these with a crown of brown cilia at the attaching point, relatively shorter stipe with longer hairs and these commonly no glandular, scaly rachis and it with longer and denser hairs, inframedial sori and glabrous sporangia.